2017
DOI: 10.1111/rec.12615
|View full text |Cite
|
Sign up to set email alerts
|

Flower visitor communities are similar on remnant and reconstructed tallgrass prairies despite forb community differences

Abstract: One common goal of habitat restoration and reconstruction is to reinstate the biodiversity found at intact reference sites. However, few researchers have examined whether these practices reinstate communities of flower‐visiting insects. This is unfortunate, as anthropogenically mediated declines in flower visitors, including bees (the primary pollinators for most terrestrial ecosystems), beetles, flies, and butterflies, have been reported worldwide. Biodiversity declines may be especially severe in North Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…(c) Bee community composition differed between restored and remnant prairies (p = 0.01), with NMDS representing community dissimilarity in multivariate space. NMDS was calculated in three dimensions but only the first two were plotted for simplicity of work supporting the concept that β-diversity and composition are important metrics for understanding diversity in conservation (Denning & Foster, 2018a;Griffin et al, 2017;Haley, 2018;Purvis et al, 2020;Tonietto et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(c) Bee community composition differed between restored and remnant prairies (p = 0.01), with NMDS representing community dissimilarity in multivariate space. NMDS was calculated in three dimensions but only the first two were plotted for simplicity of work supporting the concept that β-diversity and composition are important metrics for understanding diversity in conservation (Denning & Foster, 2018a;Griffin et al, 2017;Haley, 2018;Purvis et al, 2020;Tonietto et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations into the interaction of bees and flowering resources show contradictory responses of bees to the presence and abundance of flowering plants ( Denning & Foster, 2017 ; Potts et al, 2003 ; Tepedino & Stanton, 1981 ). For example, remnant prairies and reconstructed prairies in Kansas differed in the composition and abundance of flowering plants ( Denning & Foster, 2017 ) but showed no significant difference in richness or abundance of bees. In contrast, Tepedino & Stanton (1981) found constant and significant positive correlations between floral richness and bee richness at prairie sites in Wyoming.…”
Section: Discussionmentioning
confidence: 94%
“…Returning forbs to agricultural landscapes holds promise for maintaining pollinators (Haaland et al 2011; Ricigliano et al 2019; Baden‐Böhm et al 2022). Unfortunately, establishing the abundant, species‐rich stands of forbs necessary to support diverse pollinator communities has proven challenging (Dötterl & Vereecken 2010; Blaauw & Isaacs 2014; Denning & Foster 2017; Ouvrard et al 2018; Arathi et al 2019; Nichols et al 2019; Rivest & Forrest 2019; Vandever et al 2021; Baden‐Böhm et al 2022; Simanonok et al 2022). This study identified practical avenues for increasing numbers and abundances of forb species.…”
Section: Discussionmentioning
confidence: 99%